Methodology of Wavelets in Relativistic Heavy Ion Collisions in One Dimensional Phase Space (η-Space) - Lyashenko, V.; Mohammad, A.; Deineko, Z.; Hashim, R. (Scientific Research Publishing, 2017)
An attempt has been made to apply the wavelet methodology for the study of the results of the chaotic behavior of multiparticle production in relativistic heavy ion collisions. We reviewed the data that describes the collisions of relativistic heavy ion for the case η-space in 1-D phase space of variable. We compared the experimental data and UrQMD data using wavelet coherency. We discussed the results of the comparison.
Keywords: Wavelet Coherence; Morlet Wavelet; Phase Space